2019
DOI: 10.1177/1535370218824101
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial hypertension in connective tissue disorders: Pathophysiology and treatment

Abstract: Pulmonary arterial hypertension (PAH) is a serious complication of connective tissue disorders (CTDs), and CTD-PAH is the second cause of PAH after the idiopathic form. PAH is characterized by increased pulmonary arterial pressure and pulmonary vascular resistance, which can lead to right heart failure and death. About 90% of CTD-PAH cases are associated with systemic sclerosis (SSc, 74%), mixed connective tissue disease (MCTD, 8%) or systemic lupus erythematosus (SLE, 8%). CTD-PAH has also been reported, albe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 85 publications
2
62
0
5
Order By: Relevance
“…In our population, sMER concentration in plasma was increased in CTD-PAH, while neither that of Gas6 nor of sAxl was different according to this complication. Endothelial dysfunction is known to be a key impairment of CTD-PAH sustained by a mismatch of mediators acting as vasodilators in favour of vasoconstrictors; this process evolves with the activation of vascular remodelling towards an increase of vascular tone mediated by the endothelium and vascular smooth muscle cell (VSMC) activation [35]. Gas6/TAM interplay is known to be involved in vessel wall homeostasis: Gas6 was isolated from aortic endothelial cells, and it has a trophic effect on vessel walls; additionally, the Gas6/TAM system is activated in case of vessel damage or in human atherosclerotic plaque formation [14,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our population, sMER concentration in plasma was increased in CTD-PAH, while neither that of Gas6 nor of sAxl was different according to this complication. Endothelial dysfunction is known to be a key impairment of CTD-PAH sustained by a mismatch of mediators acting as vasodilators in favour of vasoconstrictors; this process evolves with the activation of vascular remodelling towards an increase of vascular tone mediated by the endothelium and vascular smooth muscle cell (VSMC) activation [35]. Gas6/TAM interplay is known to be involved in vessel wall homeostasis: Gas6 was isolated from aortic endothelial cells, and it has a trophic effect on vessel walls; additionally, the Gas6/TAM system is activated in case of vessel damage or in human atherosclerotic plaque formation [14,36].…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, sMER increase in these patients could be an expression of endothelial stress and dysfunction, typical of PAH. One additional possible explanation comes from the other mainstay of the pathogenesis of CTD-PAH, the presence of persistent inflammation of pulmonary vessel walls [35]. TAM receptors, indeed, are involved in regulation of innate immunity, being upregulated in activated antigen-presenting cells (APCs) through type I interferon (IFN) signalling that determines the activation of suppressor of cytokine signalling proteins (SOCS1 and SOCS3) which, in turn, dampens the inflammatory response [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining cases of CTD-PAH are typically associated with primary Sjögren's syndrome (pSS), idiopathic inflammatory myopathies (IIM) and rheumatoid arthritis (RA). 2,3 In contrast to above prevalence reports which largely consist of Caucasian populations, a large Chinese study identified SLE as the predominant cause of CTD-PAH, accounting for 58.4%, while SSc accounted for only 26.3% of cases. 4 In SSc, PAH occurs with a prevalence of 8%-12% and is the leading cause of mortality, accounting for 25%-40% of SSc-related deaths.…”
mentioning
confidence: 85%
“…4 In SSc, PAH occurs with a prevalence of 8%-12% and is the leading cause of mortality, accounting for 25%-40% of SSc-related deaths. 2,5 In SLE, the prevalence of PAH ranges 1%-5% 6 depending on the ethnicity of the population studied, with a recent Chinese study reporting a prevalence of SLE-PAH as high as 12.8%. 6 Similar to SSc, the presence of PAH in SLE is an independent predictor of mortality.…”
mentioning
confidence: 99%
“…Стійка вазоконстрикція, порушення балансу між вазодилатуючими і вазоконстрикторними речовинами, звуження просвіту спричиняє потовщення легеневої артерії, що, у свою чергу, призводить до стійкого підвищення тиску в ній. Цей судинозвужувальний ефект посилюється за рахунок зниження судинорозширювальної здатності дистального відділу легеневої артерії [10,11]. Ураження ендотелію можна розглядати як інтегративний концентратор, що запускає множинні патофізіологічні шляхи розвитку легеневої гіпертензії у хворих на ХОЗЛ.…”
Section: Conclusion Among Patients With Copd Endothelial Dysfunctiunclassified